Dampak Employee Engagement, Stress Kerja dan Iklim Organisasi terhadap Perilaku Produktif Karyawan PT. Romi Violeta - Muhammad Marwan Fadhlullah; Rifdah Abadiyah; Mochammad Rizal Yulianto (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
The purpose of this study is to investigate how PT employees' productive behavior is affected by organizational climate, job stress, and Employee Engagement. Romi Violeta, Regency of Sidoarjo. This study employs quantitative techniques on a sample of 200 workers. Purposive sampling is used to sample in accordance with the findings of the research: Employee Engagement positively impacts employee productive behavior, as does work stress, and organizational climate positively impacts employee productive behavior. Employee productive behavior also positively impacts employee productive behavior.